Extraordinary lithium storage capacity and lithiation mechanism of partially amorphous molybdenum sulfide on chemically exfoliated graphene. (10th September 2020) - Ji, Seulgi; Kim, Seong K.; Song, Wooseok; Yoon, Yeoheung; Myung, Sung; Lim, Jongsun; Jung, Ha-Kyun; Choi, Sungho; An, Ki-Seok; Lee, Sun Sook
Abstract: Molybdenum sulfides have been researched actively for application in electrochemical energy storages and conversions. For molybdenum sulfides, modifications in stoichiometry and crystal structure can lead to enhancements in their electro-chemical properties. However, even though performance of crystalline molybdenum disulfide-based lithium ion battery (LIB) anodes have been investigated extensively, amorphous molybdenum sulfide-based anodes still need to be researched. Herein we report specific capacity as high as 1872 mAh/g observed from non-stoichiometric partially amorphous molybdenum sulfide formed on chemically exfoliated graphene (MoSx -rGO) as a LIB anode. According to our analysis, amorphous part consisting [Mo3 S13 ] 2- building blocks contains an excess amount of sulfur as bridging, shared, or terminal S2 2−, which contribute significantly in enhancing the capacity of the anode. In depth electrochemical investigations and analysis suggest that MoSx -rGO undergoes a different lithiation mechanism from crystalline MoS2, and consequently exhibits such high capacity with excellent stability at least up to 200 cycles and a decreased c-rate dependence.